Factors Associated with the Occurrence of Diarrhea in Toddlers - Firyanti; Miswan; Hamidah (Journal of Health Literacy and Qualitative Research, 2024)
Environmental sanitation is important for environmental health and must be owned by every family to meet daily needs, the impact of low levels of sanitation coverage reduces the quality of human life. Poor environmental sanitation conditions are one of the factors increasing diarrheal disease, where environmental sanitation includes several factors, namely clean water quality, waste management, latrine sanitation, and liquid waste management. The type of research used is quantitative research in the form of an observational survey with the Cross-Sectional approach method, which is a study conducted with momentary observation or in a certain period of time and each study subject is only made one observation during the study. The results showed that there was a significant relationship between clean water facilities and the incidence of diarrhea in toddlers with a P-value of 0.000. The P-Value <0.05, On the advice of healthy latrines the results showed that there was a significant relationship between healthy latrines and the incidence of diarrhea in toddlers the P-Value was 0.000. The P-Value <0.05, In the suggestion of waste disposal the results showed that there was a relationship between waste management and the incidence of diarrhea in toddlers the P-Value result was 0.008. The P-Value < 0.05, In Sara ari waste (SPAL) there is a significant relationship between Sara air limbah (SPAL) with the incidence of diarrhea in toddlers the P-Value result is 0.036. P-value < 0.05. Conclusion based on the results of research that has been done on the factors associated with the incidence of diarrhea in toddlers in Ujunax` Village, Kamonji Health Center Working Area, West Palu District, Palu City.